Beach sand and the potential for infectious disease transmission: observations and recommendations. (1st July 2015) - Solo-Gabriele, Helena M.; Harwood, Valerie J.; Kay, David; Fujioka, Roger S.; Sadowsky, Michael J.; Whitman, Richard L.; Wither, Andrew; Caniça, Manuela; Carvalho da Fonseca, Rita; Duarte, Aida; Edge, Thomas A.; Gargaté, Maria J.; et al.
Abstract : Recent studies suggest that sand can serve as a vehicle for exposure of humans to pathogens at beach sites, resulting in increased health risks. Sampling for microorganisms in sand should therefore be considered for inclusion in regulatory programmes aimed at protecting recreational beach users from infectious disease. Here, we review the literature on pathogen levels in beach sand, and their potential for affecting human health. In an effort to provide specific recommendations for sand sampling programmes, we outline published guidelines for beach monitoring programmes, which are currently focused exclusively on measuring microbial levels in water. We also provide background on spatial distribution and temporal characteristics of microbes in sand, as these factors influence sampling programmes. First steps toward establishing a sand sampling programme include identifying appropriate beach sites and use of initial sanitary assessments to refine site selection. A tiered approach is recommended for monitoring. This approach would include the analysis of samples from many sites for faecal indicator organisms and other conventional analytes, while testing for specific pathogens and unconventional indicators is reserved for high-risk sites. Given the diversity of microbes found in sand, studies are urgently needed to identify the most significant aetiological agent of disease and to relate microbial measurements in sand to human health risk.